Thermal anomalies on pit craters and sinuous rilles of Arsia Mons: Possible signatures of atmospheric gas circulation in the volcano - Lopez, T.; Antoine, R.; Baratoux, D.; Rabinowicz, M.; Kurita, K.; d'Uston, L. (Journal of Geophysical Research: Planets, 2012)
Seven circular depressions named as pit craters were found in northern flank of Arsia Mons, and we report 76 new ones in the southern flank of the volcano. Their diameters range from 100 m to 1300 m and depths range from 22 to 500 m. THEMIS‐IR data reveal that some of these pit craters are 10 K warmer than the surrounding surface during night and are referred as Thermally Distinct Pit (TDP). Nighttime surface temperature variations of 10 K at this scale are common on Mars and may result from a combination of geometrical factors and/or variations of thermophysical properties. However, several observations appear to be difficult to reconcile with this view. We have thus explored the conditions for the occurrence of ∼40 km long subsurface air flow through the volcano apron and its consequences on surface temperatures. Our numerical simulations assume that cold air penetrates the apron through a slope break. It then flows upslope affecting a thickness of 6 km and finally exits 40 km away through warm pit craters and sinuous rilles. An extremely high horizontal permeability of 10−4 m2 and a vertical permeability of 10−8 m2 are used considering the anisotropic media resulting from the accumulation of lava flows and ash/scoria deposits. Without unequivocally ruling out a possible contribution of geometrical factors and thermal properties variations, these numerical simulations show that the ascending convective flow provides, at the surface, a heat flow able to sustain an excess temperature of ∼10 K. Key Points Pit craters are reported on Arsia Mons and are 10 K warmer than the surrounding This thermal pattern can be explained by a subsurface air convection Heat is transported when Raeq > 5 and the permeability anisotropy ratio = 10^4